Self-Masked Aldehyde Inhibitors of Human Cathepsin L Are Potent Anti-CoV-2 Agents - Zhu, Jiyun; Li, Linfeng; Drelich, Aleksandra; Chenna, Bala C.; Mellott, Drake M.; Taylor, Zane W.; Tat, Vivian; Garcia, Christopher Z.; Katzfuss, Ardala; Tseng, Chien-Te K.; Meek, Thomas D. (Frontiers in Chemistry, 2022)
Cysteine proteases comprise an important class of drug targets, especially for infectious diseases such as Chagas disease (cruzain) and COVID-19 (3CL protease, cathepsin L). Peptide aldehydes have proven to be potent inhibitors for all of these proteases. However, the intrinsic, high electrophilicity of the aldehyde group is associated with safety concerns and metabolic instability, limiting the use of aldehyde inhibitors as drugs. We have developed a novel class of compounds, self-masked aldehyde inhibitors (SMAIs), which are based on the dipeptide aldehyde inhibitor (Cbz-Phe-Phe-CHO, 1), for which the P1 Phe group contains a 1´-hydroxy group, effectively, an ortho-tyrosinyl aldehyde (Cbz-Phe-oTyr-CHO, 2; (Li et al., (2021) J. Med. Chem. 64, 11267-11287). Compound 2 and other SMAIs exist in aqueous mixtures as stable delta-lactols, and apparent catalysis by the cysteine protease cruzain, the major cysteine protease of Trypanosoma cruzi, results in opening of the lactol ring to afford the aldehydes which then form reversible hemithioacetals with the enzyme. These SMAIs are also potent, time-dependent inhibitors of human cathepsin L (Ki = 11-60 nM), an enzyme which shares 36% amino acid identity with cruzain. As inactivators of cathepsin L have recently been shown to be potent anti-SARS-CoV-2 agents in infected mammalian cells (Mellott et al. (2021) ACS Chem. Biol. 16, 642-650), we evaluated SMAIs in VeroE6 and A549/ACE2 cells infected with SARS-CoV-2. These SMAIs demonstrated potent anti-SARS-CoV-2 activity with values of EC50 = 2-8 micromolar. We also synthesized pro-drug forms of the SMAIs in which the hydroxyl groups of the lactols were O-acylated. Such pro-drug SMAIs resulted in significantly enhanced anti-SARS-CoV-2 activity (EC50 = 0.3-0.6 micromolar), demonstrating that the O-acylated-SMAIs afforded a level of stability within infected cells, and are likely converted to SMAIs by the action of cellular esterases. Lastly, we prepared and characterized an SMAI in which the sidechain adjacent to the terminal aldehyde is a 2-pyridonyl-alanine group, a mimic of both phenylalanine and glutamine. This compound (9) inhibited both cathepsin L and 3CL protease at low nanomolar concentrations, and also exerted anti-CoV-2 activity in an infected human cell line.